The Russian language as a mechanism for integration of the General Government of the Steppes of Russia into the common empire area (second half of the 19th — early 20th century) - Lysenko Yu.A.; Rygalova M.V.; Yegorenkova Y.N. (Вестник археологии, антропологии и этнографии, 2021)
The problem of homogeneity and integrity of the Russian Empire state territories became topical in the se-cond half of the 19th century. Its resolution was reflected in the administrative and legal integration, based on the policy of Russification and introduction of the Russian language in all spheres of life of the society. The purpose of this article is to reconstruct the mechanisms and particularities of the implementation of this policy in the Central Asian outskirts of the Russian Empire — the Governor-Generalship of the Steppes. The study is based on a wide range of hsitorical sources — regulations and paperwork, most of which have been identified in archives and in-troduced into the scientific discourse for first time. It has been revealed that the implementation of the Russifica-tion policy in the Steppe Territory followed two directions. The first one involved the introduction of paperwork management in Russian language into the local governments system. This process iniciated very actively in the beginning of the 20th century after the settlement of the legal status of the Russian language in the Russian Em-pire. Applicants for the positions of volost, aul and kishlak rulers, which were elective, were required to pass an exam on Russian language knowledge the prior to the ballot. Failure in the exam would immediately disqualify the candidate from further electoral process. The second important direction of expanding the influence of the Rus-sian language in the Steppe Territory was the educational policy related to the formation of a secular school edu-cation system and the mandatory inclusion of the Russian language course into the educational process. A net-work of Russian-Kyrgyz, Russian-aul, and missionary schools, Cyrillic-based alphabets for regional languages, educational-methodological literature in Russian were created in the region. The Russian language course be-came compulsory in programs of Muslim metebas and madrassas to raise the effectiveness of the Russification policy. Until the end of the imperial period, regional authorities failed to form a staff of ethnic officials who could speak Russian. The level of knowledge of the Russian language in the rest of the indigenous population remained extremely low, which was due to unpopularity of the Russian school system. Thus, it can be stated that the poten-tial of the Russian language as a means of integration into the common empire space was not fully utilized. At the same time, it cannot be denied, that Russian culture, historically close to Muslim peoples of the Central Asian region, embodied in the imperial educational system, played a positive role, acting as a conductor of their in-volvement in the achievements of European civilization.